EMOTIONAL INTELLIGENCE AND ACADEMIC PERFORMANCE: A CASE STUDY AT NAZARBAYEV UNIVERSITY AND KAZAKH-BRITISH TECHNICAL UNIVERSITY - Malik, Zarina; Sembayeva, Zhanel (Nazarbayev University, Graduate School of Public Policy, 2021)
The purpose of this paper is to examine the relationship between academic performance and emotional intelligence using a primary dataset from Nazarbayev University (NU) and Kazakh-British Technical University (KBTU). We address the issue of low EQ scores associated with the performance of STEM students. For this, we adopt Trait Emotional Intelligence Questionnaire designed by Petrides (2009) and conduct descriptive statistics, multinomial logistic regression, ordered logistic regression, and binary logistic regression analyses. The sample consists of 245 undergraduate degree students’ responses from two universities. We conclude that the effect of higher EQ scores on academic performance is: (a) positive for STEM students, (b) positive for female students, (c) negative for male students, (d) negative for female sophomores, and (e) positive for male sophomores. We argue this constitutes a national public policy problem given the high demand for emotionally intelligent STEM graduates in the labor market. We are unaware of primary studies on the EQ-academic performance relationship in Kazakhstan.
Keywords: Type of access: Open Access; emotional intelligence; STEM students